(untitled) (Bangladesh Journal of Urology, 2025)
Background: Untreated ureteropelvic junction blockage (UPJO) may lead to hydronephrosis and renal dysfunction. UPJO is usually treated by open pyeloplasty (OP), which has a 90% success rate. This surgery requires a large flank incision and has pain, postoperative morbidity, and a long recovery. However, laparoscopic (LP) UPJO treatment is minimally invasive. Objective: The aim of this study is compare operative outcome between laparoscopıc and open pyeloplasty in adults in management of UPJO. Method: This prospective observational study was conducted at the Urology Department of National Institute of Kidney Disease and Urology from February 2022 to January 2023 over a period of one year. During preoperative counseling, patients were presented with two options for surgery: open or laparoscopic pyeloplasty. The patient was given the freedom to choose the technique they preferred. Twenty-five patients agreed to undergo open pyeloplasty while others opted for laparoscopic pyeloplasty. To maintain an equal number of participants, twenty-five patients were selected to undergo laparoscopic pyeloplasty. The study was approved by the ethical committee of NIKDU, and written consent was obtained from each patient. Result: There was no significant differences in age, gender and BMI between the two groups. Surgical site 32.0% in right and 68.0% in left in both the groups. Duration of symptoms little higher in OP but not significantly. There were no significant differences in grade of hydronephrosis, anteroposterior diameter of pelvis renalis, parenchymal thickness, diuretic renography and eGFR between the two groups. Regarding etiology, aperistaltic segment was 56.0% in LP and 64.0% in OP, crossing vesssels was 28.0% in LP and 32.0% in OP, stricture was 16.0% in LP and 4.0% in OP (p>0.05). Operative time and blood loss was significantly higher in LP than OP. Hospital stay and analgesic requirement was significantly lower in LP than OP. VAS was significantly lower in LP than OP on 2nd POD as well as on 3rd POD. Improvement of anteroposterior diameter of pelvis renalis was significantly lower in LP than OP. There was no significant difference in post-operative improvement of DRF between the two groups. eGFR improvement was significantly less in LP than OP. Conclusion: Pyeloplasty success in adults is measured by pain relief. Our study found better APD improvement and shorter operative time in the OP group, while the LP group had less blood loss, shorter hospital stays, and required fewer analgesics. Bangladesh J. Urol. 2024; 27(2): 125-131